Epitope mapping by solution NMR spectroscopy‡. Issue 6 (27th February 2015) - Bardelli, M.; Livoti, E.; Simonelli, L.; Pedotti, M.; Moraes, A.; Valente, A. P.; Varani, L.
Abstract : Antibodies play an ever more prominent role in basic research as well as in the biotechnology and pharmaceutical sectors. Characterizing their epitopes, that is, the region that they recognize on their target molecule, is useful for purposes ranging from molecular biology research to vaccine design and intellectual property protection. Solution NMR spectroscopy is ideally suited to the atomic level characterization of intermolecular interfaces and, as a consequence, to epitope discovery. Here, we illustrate how NMR epitope mapping can be used to rapidly and accurately determine protein antigen epitopes. The basic concept is that differences in the NMR signal of an antigen free or bound by an antibody will identify epitope residues. NMR epitope mapping provides more detailed information than mutagenesis or peptide mapping and can be much more rapid than X‐ray crystallography. Advantages and drawbacks of this technique are discussed together with practical considerations. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Characterization of antibody epitopes has useful implications for both basic research and the biotechnology sectors. Solution NMR spectroscopy is a powerful and yet relatively unknown tool for the determination of epitopes. The basic concept is that differences in the NMR signal of an antigen free or bound by an antibody can identify epitope residues. The article describes advantages and drawbacks of this approach, including practical considerations.